The Effect of Work Discipline and Organizational Culture on Work Productivity With Competency as an Mediation Variable in Sand Mining Companies in Pabuaran District, Serang, Banten - Ahmad Karnain; Gema Ika Sari; Udin Suadma (STIE Amkop Makassar, 2026)
This study aims to analyze the influence of work discipline and organizational culture on work productivity, with competency as a mediation variable, at a sand mining company in Pabuaran District, Serang Regency, Banten Province. The research method used was a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis. The population in this study was all 84 employees at three sand mining companies. A census sampling technique was used to select the entire population. The results showed that work discipline had a positive and significant effect on work productivity (β=0.570; t=5.931; p=0.000) and on competency (β=0.429; t=3.771; p=0.000). Organizational culture also had a positive and significant effect on work productivity (β=0.175; t=2.467; p=0.014) and on competence (β=0.315; t=2.779; p=0.006). Competence was shown to have a positive and significant effect on work productivity (β=0.280; t=3.448; p=0.001). Furthermore, competence mediated the effect of work discipline on work productivity (β=0.120; t=1.976; p=0.049) and the effect of organizational culture on work productivity (β=0.088; t=2.653; p=0.008). This study implies that work productivity can be increased by strengthening work discipline and improving organizational culture, while still considering competency development as a factor that strengthens this relationship. These efforts are expected to encourage more optimal, effective, and high-quality work productivity in the sand mining sector.